Hooked on the metaverse? Exploring the prevalence of addiction to virtual reality applications - Barreda-Ángeles, Miguel; Hartmann, Tilo (Frontiers in Virtual Reality, 2022)
Similar to debates about other new media technologies in the past, with the popularization of virtual reality (VR) technologies, concerns are raised about their potential to breed media addiction. In response to these concerns, the aim of this research was to provide a first examination of the prevalence of addiction to VR application use. An online survey was conducted among frequent VR users (N = 754), and measures of the different components of addiction were obtained, as well as demographics, hours of weekly use, type of apps used, and feelings of spatial presence and embodiment during VR app use. The results indicate that between 2% and 20% of users reveal compulsive VR use, depending on the classification criteria used. These prevalence estimates are similar to those of other activities such as the use of (non-VR) video games or the use of social networking sites. Therefore, the results suggest that VR applications do not have a higher addictive potential than other more traditional technologies. However, feelings of embodiment when using VR positively predict addiction. This may suggest that future developments of VR technology could, perhaps, also increase its addictive potential compared to other technologies.